Natriuretic peptides promote glucose uptake in a cGMP-dependent manner in human adipocytes - Coué, Marine (Sci Rep, 2018)
Robust associations between low plasma level of natriuretic peptides (NP) and increased risk of type 2 diabetes (T2D) have been recently reported in humans. Adipose tissue (AT) is a known target of NP. However it is unknown whether NP signalling in human AT relates to insulin sensitivity and modulates glucose metabolism. We here show in two European cohorts that the NP receptor guanylyl cyclase-A (GC-A) expression in subcutaneous AT was down-regulated as a function of obesity grade while adipose NP clearance receptor (NPRC) was up-regulated. Adipose GC-A mRNA level was down-regulated in prediabetes and T2D, and negatively correlated with HOMA-IR and fasting blood glucose. We show for the first time that NP promote glucose uptake in a dose-dependent manner. This effect is reduced in adipocytes of obese individuals. NP activate mammalian target of rapamycin complex 1/2 (mTORC1/2) and Akt signalling. These effects were totally abrogated by inhibition of cGMP-dependent protein kinase and mTORC1/2 by rapamycin. We further show that NP treatment favoured glucose oxidation and de novo lipogenesis independently of significant gene regulation. Collectively, our data support a role for NP in blood glucose control and insulin sensitivity by increasing glucose uptake in human adipocytes. This effect is partly blunted in obesity.